A study of validation of competitive abilities scale of judo competitors by using AHP - Maekawa, N.; Ito, K.; Ishii,K.; Koshino, T.; Yazaki, R.; Tamura, M.; Hirose, N. (Research Journal of Budo, 2015)
The previous Maekawa et al.`s9) investigation on the validation of competitive abilities scale of judo competitors determined nine items such as general motor ability, mental toughness, attention to form, stamina, tactics, assertiveness of the athlete in applying kumi-te, proper kumi-te style, standing defense, and mat skills. The aim of this study is to develop a scale on competitive ability and to verify the validity of the scale by using Analytic Hierarchy Process (AHP) based on those nine items. As a result, data ranked by the total score of the competitive ability scale had a high correlation with predicted competition results by AHP (respectively, p<0.001, for all; Spearman`s Rank Test). Thus, this study showed that the scale on competitive ability was effective by using AHP.